2022
DOI: 10.3389/fsurg.2022.923427
|View full text |Cite
|
Sign up to set email alerts
|

Lung Immune Prognostic Index Could Predict Metastasis in Patients With Osteosarcoma

Abstract: BackgroundThe lung immune prognostic index (LIPI), composed of serum lactate dehydrogenase (LDH) and the derived neutrophil to lymphocyte ratio (dNLR), is a novel prognostic factor of lung cancer. The prognostic effect of the LIPI has never been verified in osteosarcoma.MethodsWe retrospectively reviewed the osteosarcoma patients with metachronous metastasis from January 2016 to January 2021 in West China Hospital. We collected and analyzed the clinical data and constructed the LIPI for osteosarcoma. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Fourteen independent clinical studies conducted specifically on OS have shown that the higher an NLR becomes, the shorter the survival becomes [294][295][296][297][298][299][300][301][302][303][304][305][306]. The extraordinary nature of this association of a higher NLR with a shorter survival in adult and pediatric OS should be fully appreciated.…”
Section: Ticomentioning
confidence: 99%
“…Fourteen independent clinical studies conducted specifically on OS have shown that the higher an NLR becomes, the shorter the survival becomes [294][295][296][297][298][299][300][301][302][303][304][305][306]. The extraordinary nature of this association of a higher NLR with a shorter survival in adult and pediatric OS should be fully appreciated.…”
Section: Ticomentioning
confidence: 99%
“…The lung immune prognostic index (LIPI), composed of the derived neutrophil-to-lymphocyte rate (dNLR) and LDH, was reported to be associated with the survival of patients with a variety of cancers. [12][13][14][15][16][17] Although the precise mechanisms underlying the association of LIPI with the survival of cancer patients are unclear, the dNLR is thought to reflect systemic inflammation and therefore might be a potential surrogate marker for immune status. 12,18 LDH is associated with the proliferation of cancer cells via various mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no effective method to evaluate the status of pulmonary metastasis and predict the probability of metastasis in patients with OS. 8 The global annual incidence of osteosarcoma is about 3-4 per million. 9 There is a substantial amount of patients with OS in the world, but the evidence-based information about OS patients is still limited and controversial, and there are few nomogram models being reported for the prognosis of OS patients, let alone models for predicting the risk of pulmonary metastasis of OS.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no effective method to evaluate the status of pulmonary metastasis and predict the probability of metastasis in patients with OS. 8…”
Section: Introductionmentioning
confidence: 99%